Bankacılık sektöründe kriz ve risk yönetimi: Türkiye uygulaması - Okay, Esin (My University, 2002)
The purpose of this dissertation is to provide a selective review of banking crisis in Turkey, the factors behind the depression and the solutions through risk management. The study points out the types of problems arising from banking sector's exposure to loss and how these problems may be approached and solved. Banking system in Turkey that has already turned out to collapse in the last few years cannot get rid of a decline caused by bank shocks and failures. At the same time, the growing economic crisis in Turkey enhances the depression of banks. Turkish banking sector is always supported by reforms and reconstruction along with the economic developments, but the performance, growth and financial structure of the system are still under influence leading to heavy losses. Unfortunately, banks are headed for a struggle to survive as the consequences change. Especially, because of increasing effects of macroeconomic instability, financial impasse and frequently changed regulation and implementations during economic crisis, the sources are limited and banking is mismanaged. Also, banking sector in Turkey still experiences serious deficiencies caused by the historical evolution of the system in the past. As a result, the banking sector loses credit and esteem. Turkish banks have worked on enriching their system and adapt themselves to changes in recent years but the level of sophistication is not very high. Additionally, banking sector does not seem to assume and understand risk management and its role to provide efficiency to the bank management. In order to relieve the system from the problems, banks have to pay more attention to risk management. Certainly, financial risks and risk-taking emerge from financial operations. At this point, risk management happens to be a perspective to deal with the risks and potential losses. The body of the thesis illustrates a background to show that banks are to fail without risk management. Banks in Turkey do not obey the standard risk financing techniques, methods of controlling and financing exposures, new financial techniques. Risks are not widely shared and risk pricing and enabling is not performed well by Turkish banks according to their ability and willingness to absorb them. The depression of banking sector in Turkey will drive back and banks will recapture public confidence in the system again if risk management is taken account. Nowadays, the most striking trend in international banking is risk management. The 1980s and 1990s witnessed a major transformation in the international financial markets. The advent of more complex and dynamic transactions have substantially increased uncertainties in the marketplace. In today's environment, dominated by a dynamic, aggressive financial service industry, market participants are exposed to greater financial risks than before. A string of disaster stories dominated the financial news coverage during the last two decades. A variety of factors could be cited as possible causes of these events. They include shortcomings in economic policy, inadequate supervision and, in most cases, poor risk management by the market players themselves. Beyond that, the basic issue is the financial system's vulnerability to unforeseen events. Much more striking is that the world is tremendously changing. These changes can be good or bad for those affected by them. The first reason is the globalization of the international markets. Markets all over the world are becoming consolidated into a vast world market as obstacles to the free movement of capital are gradually being removed. This can be seen in the present global crisis, which arose because problems occurring in one region of the world promptly made them felt by markets and investors in other regions. Globalization reorganized some concepts such as stabilization, risk-taking, supervision and regulation of banking systems, market discipline, public guaranty on deposit, moral hazard and adverse selection. As a result of financial developments, every trading institution, including central banks, has become more exposed to changes all over the world economies and financial markets. Indeed, the recent Asian financial crisis revealed that the financial and economic stability of emerging market economies is extremely vital for global financial and economic stability. Banking business and banking transactions have become very complex. Development of off-balance sheet transactions and derivative markets had an enormous impact on the banks' balance sheet structure, level and variety of risks to which they are exposed. Based on these developments, the importance of derivative instruments in banks' risk profile has increased. It is widely accepted that the risks are arising from globalization and that there are losers as well as winners in this arena. The process of globalization does not evolve equally worldwide. Some countries obtain great benefit from the process, mainly driven by their rapid integration into the global economy relative to other countries. In other words, the integrated global economy does not guarantee that the benefits of globalization are shared by the all countries involved in the process. More importantly, opportunities provided by the globalization process are not always beneficial, as shown by the recent crises. Hence, the process of globalization always carries social, economic, financial, cultural, and even political risks in addition to the risk of contagion. There are several reasons for this situation. Some of them are beyond the control of the countries involved such as external shocks and other unexpected changes in external environment. Indeed, most of these reasons are due to, - weak macroeconomic and financial policies implied, - inconsistencies in domestic policies, - increased vulnerability of national economies to external shocks, - higher international capital mobility (i.e. higher sensitivity of international capital flows among economies), - higher volatility of exchange rates due to integrated financial markets, which hits real sectors of economies. As countries' economies become more vulnerable to external changes, they are exposed to shocks and crises with severe consequences both in financial and real sectors, as well as facing heavy social costs. Instability emerging in one country can spread almost instantly to other countries. There is no doubt that every country faces its own challenges that are directly affected by their particular economic and social conditions. Positions taken in one country are now being hedged in another and this so-called proxy hedging of country risks spreads shocks and crises across national borders. As a result of this, even a country with no direct exposure to the country in crisis could find itself in deep trouble. In fact, the most recent crises in East Asia and Russia have reminded us how rapidly and compellingly a financial crisis can erupt. Another reason is that the international markets have become much more volatile. Volatility, which means the fluctuation of market prices and ratios, is one of the principal sources of financial risk. When market volatility increases, market participants are exposed to greater uncertainty--and greater risk. Still another change of conditions in the international markets is the appearance of new forms of investment with very complex structures. The great variety of these investment tools has led to the development of still others, like derivative instruments, aimed at reducing the degree of risk associated with several financial transactions. Derivative instruments are being more and more widely used in the hope of reducing risk in the financial markets, but the losses coming from derivative operations have also begun to increase. The worldwide increase in the supply of loanable funds has also played an important part in the upsurge of financial risks. This surge, in combination with greater uncertainties, has caused much greater losses due to the materialization of financial risks. In the 1990s especially, such losses have frequently resulted from financial scandals. The recent collapse of Long-Term Capital Management has clearly shown that not even having Nobel-prize winning managers can always reduce the risk. Finally, one of the principal reasons for the increase in financial risks is to be found in the greater intensity of international competitiveness. Credit risk in particular has become more complicated since the banking sectors of developed and emerging market countries began to compete in the same arena, and since the larger banks began to compete intensively against non-bank financial institutions. Every one of these developments has fundamentally affected national and international banking systems. More effective risk management by banks and other financial institutions has become vital for preserving the financial stability of both domestic and international markets. The changes show that market participants and departments responsible for financial control, and also portfolio and other managers, are often unaware of some of the risks to which their institutions are exposed. For all these reasons, the sound measurement of financial risks and methods for their effective management have become an absolute necessity. It is also important to make regular announcement of information on which market participants can base sound decisions about a bank's financial standing and risk structure. It is well known that markets have a natural disciplinary mechanism, which rewards banks that manage their risks effectively and penalize banks that show themselves to be risky. Everybody knows that the successful operation of this mechanism depends on the regular dissemination of information making banks and the banking system transparent and allows market participants to arrive at sound decisions. Therefore, change leading to risk -the prospect of gain or loss- and the risk of loss are something that one should be aware of. To be aware of risks does not mean eliminating them completely, which is certainly impossible, nor does it mean that there is nothing to do about risks and accept consequences fatalistically. It means that risk must be managed. To manage risks one must decide what risks to avoid and how to avoid them; what risks to accept and on what terms to accept them; what new risks to take on and so on. Both theory and practice of risk management have developed enormously in the last two and a half decades. The theory has developed to the point where the risk management is now regarded as a distinct sub-field of the theory of finance and risk management has become a separate subject in the master's and MBA programs. The subject has attracted a huge amount of intellectual energy not just from finance specialists but also from specialists in physics. As a result of these developments along with the globalization of financial markets and changes, every trading institution has become more exposed to changes all over the world economies and financial markets. This has led all institutions including central banks to develop new processes in their organizations to manage the risks in a more systematic way, although they used to have had implicit risk management practice. Parallel to these developments in risk management, the practice of reserve management by most of the central banks has changed significantly over the last decade. Once characterized by passive short-term investment strategies to preserve principal value and maintain maximum liquidity, many central banks now use a broad range of instruments, extend their portfolio duration and develop performance benchmarks. This increased attention to risk management and new approach to reserve management by central banks has come about not because of any change in central bank missions, but because of the growing recognition that the conduct of core businesses inevitably involve exposure to financial risks and also because of increased attention to the contribution of central bank profits to national treasuries. Advances in financial risk management brought more scope for central banks to consider increasing their portfolio returns together with maintaining the desired level of liquidity, which is the primary target for central banks. Then, the important question of how an effective risk management system can be developed comes out. The answer to this question does not change depending on the objectives and the size of the institution. Only for more complex organizations, a more extensive technological infrastructure is needed. To have a well established, in other words, efficient risk management system, first we need to develop the risk culture within our organizations meaning that we need to make sure that at all levels every person understands the risks the institution is exposed to. It is the responsibility of top management to provide that kind of information by having a clear approach to risk, its appetite for risk and assigning responsibility for assuming and controlling risks. Therefore, the first step in risk management process is to identify the risks the institution is exposed and to quantify those risks. Effective risk management requires that a consistent methodology be developed for analyzing risk. Important steps in risk management analysis are as follows: - Identifying the key financial flows; - Determining the appropriate time horizon; - Setting a benchmark; - Defining the institution's return objectives and views toward risk. As well-known, most progress has been made in the measurement of market risk and much work is now being done in many places to construct models for a better management of credit risk. Difficulties with credit risk measurement lies in the lack of statistics about individual default probabilities. Even if these default probabilities can be estimated reasonably accurately, it is still rather difficult to combine them into portfolio assessments. The reason for that partly stems from the lack of statistical knowledge about the interaction between variables. Therefore, the models mostly tend to rest on simplified assumptions based on subjective judgments. It should be emphasized that it is necessary to combine them with sound judgment and common sense. Since these models are no more than simplified and limited image of the real world, they are better to be used having this fact in mind and the decisions must be taken not solely relying on the results of these models. The results should be supported with scenario analysis, stress testing and most importantly with the sound judgment of the decision makers. Another important aspect of risk analysis is that it should be integrated, meaning that the analysis results for different risk types should be comparable with each other to facilitate decision-making. It necessitates that the assumptions, data, valuation models used in analyzing different types of risks be the same or at least consistent with each other. Organizationally, the integration of risk analysis requires that there be a single, common risk management authority for the whole organization. At the beginning, it might not be easy to look at risk on an institution-wide basis. Since it requires a considerable amount of capital to be invested either in terms of technology, or in terms of staff. Besides that, the risk management system must be flexible enough to adjust to the rapid developments in this area. So, at the end, the risk management system should be established in a way to allow the management to compare risk on a consistent apples for apples basis even for those risk factors such as operational and legal risk, where there limited data is available. The management not only has to set standards for its risk policies but also has to ensure that they are disseminated to and understood by the staff who are affected by them. It is worth to restress since it is impossible to launch the risk culture without ensuring that kind of communication channels in the organization. Reporting and monitoring is really important to check the system's efficiency. Because of this, the risk management function has to have an independent reporting line to provide assurance that the institution is assessing its risks effectively, and is complying with its own risk management standards. With this functionality, reporting is the key component of any risk process, because it is basically the window into the risk management results and the means of communicating risks the institution is exposed to. Therefore, data collection and processing need to be highly efficient so that accurate risk results are available in time and within the necessary level of confidentiality. The task of maintaining the stability of national and international banking systems has come to require new arrangements and dispositions in the banking sector. To lead the way for progress in this area, a committee was established, led by the Bank for International Settlement (BIS) and made up of central banks and banking supervisors from several countries. Almost all of the proposals that ultimately originated in the work of this Basle Committee have been adopted for the banking systems of many countries, even though the Committee has no power to apply sanctions. One of the first accomplishments of the Basle Committee was a study of banks' capital adequacy. Issued in 1988, under the title International Convergence of Capital Measurement and Capital Standards, this report was soon endorsed by many countries. Also known as the Basle Capital Accord, the study took account of credit risk. Although the variety of risks in the international markets is increasing, credit risk is still the most significant risk category for banks. Credit risk means the probability of defaulting on one's obligation to the other party in any transaction. As mentioned before, the growth of competitiveness in the international credit markets in recent years, the active participation of non-bank financial institutions in these markets, and borrowers' resort to the capital markets for loans at lower cost, have all brought about a considerable narrowing of profit margins in credit transactions. This has forced the banks to make more loans in order to have a competitive edge. But they have encountered credit problems due to adverse developments in the economic and financial conditions. All these developments have resulted in the design of new methods for more effectively evaluating the risks and yields of credit transactions. Besides, creating credit rating models for use within banks, these efforts have produced analytical methods calling for intensive data analysis such as retrospective analysis of credit losses, models of bankruptcy probabilities, and stress tests. Credit risk has traditionally been considered to be the most important risk for a commercial bank and poor asset quality has probably been the cause of more bank failures than any of the exposures discussed above. As well as the degree of risk involved in particular types of transaction, the assessment of credit risk involves considering the total size of exposure to any given counterpart or group of connected counterparts, settlement risk and potential country risk and cross-border problems. The analysis, which follows, seeks to classify the relative degrees of credit risk arising from different off-balance-sheet activities according to three categories of risk. It should be stressed that these judgements are made in the light of present knowledge and may well need to be revised as a result of experience. Full risk where the instrument is a direct credit substitute and the credit risk is equivalent to that of an on-balance-sheet exposure to the same counterpart; - medium risk where there is a significant credit risk but mitigating, - circumstances which suggest less than full credit risk, - low risk where there is a small credit risk but not one that can be ignored. Effective management of the credit risks of banks and determining how much capital must be held against contingencies that could arise from such risks are very important for the soundness and stability of the banking sector. The 1988 Basle Capital Accord was the fruit of the work directed to this aim. The Accord targets a bank's capital holdings as a proportion of the credit risk of their on-balance-sheet and off-balance-sheet business. For this purpose, investment instruments were classified into five main categories according to their risk, and a risk coefficient assigned to each group. The weighting formula for asset risk was intended to determine the capital coverage needed for a bank's exposure to credit risk. But this arrangement dating from 1988 proved ineffective against newer developments emerging during the last decade, and work continues particularly at the BIS on how to reduce credit risk. Besides credit risk, the main risk categories that have been identified in transactions and markets: such as market risk, exchange rate risk, interest rate risk, liquidity risk, operational risk, country risk, legal risk, hedging risk. Once the risk is identified, measuring it accurately is generally accepted as the next step in preventing it from happening. The rapid progress of information technology in recent years has brought new risk measurement models to aid in the measurement of market risk. The increasing use of financial instruments, which do not involve the acquisition by banks of conventional on-balance-sheet assets, raises some difficult questions for individual bank managements, for supervisory authorities and for accountants. It also raises important macro-prudential issues concerning the financial system as a whole. While the pace of developments appears quicker in some countries than others, banks generally are becoming more deeply involved in an array of novel instruments and techniques. Some of these are technically very complicated and are probably only fully understood by a small number of traders and market experts; many pose complex problems in relation to risk measurement and management control systems; and the implications for the overall level of risk carried by banks is not easily assessed. The worldwide total of commitments is very large indeed. BIS has concluded that the rapid growth of commitments represents a significant additional risk to banks' funding strategies. Many commitments are callable entirely at the borrower's option and many are most likely to be called when other markets (in particular the capital markets) are reluctant to meet the borrower's needs. It is therefore possible that a bank might be faced with large and perhaps unexpected calls under commitments at a time when markets are unreceptive to its needs for additional funds. To the extent that the growth in commitments represents a structural shift in borrowing patterns, such that banks move away from direct lending and increasingly towards a back-stop function, it may prove difficult to raise large sums at short notice to meet these commitments. For all these reasons, banks will need to be particularly cautious in their funding management. Banks may wish to assess (and set limits on) their total volume of commitments in terms of their perceived funding capacity, perhaps assessing this on a worst case basis and revising it in line with market conditions, actual draw-down and developments in borrowers' creditworthiness. It may be that, wherever possible, banks will seek committed lines for their own use to reduce their funding mismatch. Aside from funding difficulties and the liquidity of the cash markets there is also a degree of concern about the liquidity of some of the newer markets (for example options, futures, forward rate agreements and swaps). Not all these markets are yet tried and tested and banks will need to monitor their positions in them very carefully. Banks conduct a wide variety of activities off the balance sheet, which have an impact on their interest rate exposure. Many such activities, for example swaps, options and forward rate agreements, may be entered into as a hedge against on-balance-sheet interest rate exposures, or as banks see, arbitrage opportunities open up between cash and futures markets or between one futures market and another. Swaps in particular will often be provided as a product in their own right. Some transactions may be undertaken with the deliberate aim of increasing net interest rate exposures. Where a bank acts as a market-maker in these instruments, this may lead to an increase in interest rate as well as in credit exposure. In principle, it should be possible for banks to incorporate position risks arising specifically from off-balance-sheet activities into any system designed to measure overall interest rate exposure. Banks employ a variety of techniques ranging from simple gap limits to risk point systems of various degrees of complexity. All these approaches make implicit and explicit assumptions, which must be constantly reviewed and tested. The degree of complexity and sophistication that is necessary or appropriate for an interest rate risk measurement and control system will vary between banks. Systems, however, need to be capable of capturing all the interest rate exposures of a bank. Banks also need to be able to perform sensitivity analyses, so that management can estimate the effect of a given change in interest rates. Those banks which engage in large volumes of interest rate swap transactions and other significant off-balance-sheet interest arbitrage will also have to consider how to measure and control basis risk. Options give rise to particular concerns because of their unique risk distribution characteristics and the technical difficulties involved in risk hedging. The distribution of both market and credit risks as between writers and buyers of options is asymmetrically. The buyer of an option has in theory the possibility of an unlimited profit, but his potential loss is limited to the amount of premium paid. Conversely, the writer of an option is in principle exposed to the possibility of unlimited loss if he does not hedge the exposure, while his maximum potential profit is limited to the premium income received. This asymmetry is reversed in the case of credit risk. The writer of an option has no credit risk once the premium payment has been received since the buyer has no obligations to carry out; the buyer, however, is exposed to the writer's ability to perform throughout the life of the option. Managing, hedging and pricing options require considerable statistical and mathematical expertise. The finance industry has increased its awareness of risk management practices as a result of high profile failures abroad, advances in technology and developments in the regulatory process. There has been an increased emphasis on the quality of internal management systems as a key defence against large trading losses such as those experienced at Barings, Daiwa, Sumitomo and National Westminster. Advances in technology have enabled institutions to develop more sophisticated systems for monitoring and controlling risk. Regulatory developments have contributed by recognising the more rigorous risk management methodology contained in banks' internal models for the purpose of setting market risk capital standards. With the shift in focus to risk management, there has been ever increasing attention devoted to the quantitative rocket scientist elements underlying trading products and risk management methodologies. This thesis however, steps away from the mathematics and looks at the qualitative framework surrounding the quantitative analysis. It analyses at a practical level the issues involved in risk management across an organization. It highlights the increasing emphasis on risk management systems, methodologies and practices by institutions and regulators. The study looks at the significance of the control function in the risk management framework and outlines a number of trends including the growing importance of the risk control unit. It briefly touches on the major issues underlying asset and liability management. Banks are moving towards downloading relevant information from various systems to a data warehouse which is then used to generate market and credit risk, capital and other management reporting. With advances in technology and the increasing emphasis on risk management, there is a move towards developing more sophisticated systems. The proliferation of market risk software packages has meant that even the smaller institutions now have access to relatively sophisticated market risk management systems. One of the real constants in the industry is the continual upgrading of systems as markets and conditions change. An example of this is the use of technology such as object-oriented software that can be easily adapted to incorporate new products and risks. Risk measurement methodologies are becoming increasingly sophisticated. The most widely accepted of these is the Value-at-Risk model, called VaR for short. VaR is the maximum loss that can occur in the value of a portfolio having a certain investment horizon under a certain probability. Since it is a simple and clear-cut concept, the VaR model is widely used for measuring market risk. It permits comparison of the market risk of different investment instruments, so that portfolio performance can be evaluated in terms of the risk undertaken. Especially for measuring market risk to determine capital adequacy, this model has become a necessity in many countries and financial institutions. VAR models aim to measure the potential loss on a portfolio that would result if relatively large adverse price movements were to occur. VaR is used predominantly as a high level management tool with structural limits, such as basis point values and net open positions, used to influence trader behaviour. VAR is, however, starting to be driven down to the dealer level as traders become more sophisticated and measures such as risk adjusted performance (based on VAR) shape behaviour and move capital to its most efficient use. Since 1998, U.S. commercial banks with significant trading activities have been required to hold capital against their defined market risk exposure. Under the internal models approach embodied in the current regulatory guidelines, the capital charges are a function of banks' own VaR estimates. VaR estimates are simply forecasts of the maximum portfolio loss that could occur over a given holding period with a specified confidence level. Clearly, the accuracy of these VaR estimates is of concern to both banks and their regulators. Two hypothesis-testing methods for evaluating VaR estimates have been proposed, namely, the binomial and the interval forecast methods. For these tests, the null hypothesis is that the VaR estimates in question exhibit a specified property that is characteristic of accurate VaR estimates. The tests generally have low power and are thus prone to misclassifying inaccurate VaR estimates as acceptably accurate. An alternative evaluation method, based on regulatory loss functions, is proposed. Magnitude loss functions that assign quadratic numerical scores when observed portfolio losses exceed VaR estimates are shown to be particularly useful. Simulation results indicate that the loss function evaluation method is capable of distinguishing between VaR estimates generated by accurate and alternative VaR models. The additional information provided by this method as well as its flexibility with respect to the specification of the loss function make a reasonable case for its use in the regulatory evaluation of VaR estimates. Another method widely used for measuring market risk is Scenario Analysis. Scenario Analysis is a technique used to see how the value of a portfolio would be affected by various probable changes in market conditions. A last widely used method for measuring risk is the Stress Test method. The Stress Test is used to estimate how the value of a portfolio would be affected by large, unexpected fluctuations in the markets, such as have been observed during the global crisis which still affects the world economy. Though similar to Scenario Analysis, the Stress Test mainly aims to predict the maximum value that would be lost by a portfolio under certain extraordinary market conditions. The success of this method depends on successfully predicting market conditions. A comprehensive stress testing program is an essential supplement to a VaR model. Stress testing involves subjecting trading portfolios to unexpected but possible shocks in market or political conditions. This enables an institution to evaluate its capacity to absorb potentially large losses and to identify steps that it can take to reduce its risk and conserve capital. The move moving towards more regular stress testing is in part being driven by the market risk capital requirements whereby banks using internal models will be required to submit the results of their stress testing scenarios to the Reserve Bank on a quarterly basis. For a number of institutions with large balance sheets the interest rate risk lying within the banking book is substantially greater than the market risk sitting within the trading book. Therefore, it is essential that a comprehensive risk management framework be developed, that effectively identifies, measures, monitors and controls interest rate risk exposures. In general, increasing resources and attention is being devoted to balance sheet risk management. Systems used are becoming more sophisticated as institutions move away from traditional gap analysis to simulation of net interest income and market value of equity. State of the art techniques including simulation and option type analysis are being used to analyse the risks underlying the balance sheet in greater detail. The aim is not only to manage these risks but also add value to the entire process. The integrity and timeliness of data on current positions is a key component of the risk measurement process. One of the biggest hurdles is obtaining accurate, timely data across the entire operation from retail banking to Treasury. The problem arises because of the large number of disparate systems that are used. This data aggregation problem implies that detailed analysis of interest rate risk is usually only conducted on a monthly basis. In the interim, however, major movements in the balance sheet are monitored. At smaller institutions, the problem of aggregating data over a number of systems is substantially reduced and this enables the management of interest rate risk on a more frequent basis, often using simpler techniques. The complexity involved in modelling interest rate risk has meant that even Basle Committee on Banking Supervision has deferred the development of a capital standard. The complexity arises from the fact that as well as technical assumptions and economic forecasts one needs to take into account customer behavioural patterns, such as break?outs and prepayment behaviour, which is hard to model accurately. In addition, the difficulties associated with determining objective mark to market values for assets and liabilities (for example, loans) introduce another level of subjectivity to the process. Despite these complexities, the magnitude of potential interest rate risk on the balance sheet implies that banks as well as supervisors will devote more attention to this area over the next few years. The question of whether transactions should be classified as trading or investment is a widely debated issue. The fundamental problem is that there are no clear rules that define the boundary between investment and trading positions. The implementation of the market risk guidelines will partly address this issue, as each bank will be required to agree a trading book policy statement with the Reserve Bank. The statement will establish which activities constitute the trading book and the arrangements in place to prevent inappropriate switching of transactions between the trading and banking books. The difficult issue of defining a trading book within the context of the broad structure of a bank will be addressed in terms of looking at the substance behind the words of a trading book policy statement. A well acknowledged trend is the maturing of many of the traditional trading markets. As competition has increased and with products becoming more commoditised, margins have declined and this has lead to a fall in profitability. There has also been a decline in proprietary trading in many banks as a result of lower margins and generally lower levels of market volatility. To counter this, there has been a push to increase income by expanding and generating more value from the customer franchise. The rationale is that customer generated business is more sustainable and significantly less volatile than proprietary trading. Treasuries are moving away from being perceived as a simply another profit centre to playing an important role in the overall banking/ customer relationship. For example, banks are taking an active role in educating customers about the risks involved with various products, especially in relation to exotic instruments. Banks visit corporate clients and make presentations to senior management about the nature of the products and the risks involved. A similar process of education is occurring internally as banks make Board members more aware of the risks underlying both the Treasury and asset and liability management functions. In short, four forces are driving increased awareness of risk management practices: high profile trading disasters; regulatory developments; advances in technology; and the trend away from proprietary trading towards customer generated business. The large losses at financial institutions demonstrated that it is often operational risk and a breakdown of basic internal controls that pose the greatest threat. This has driven an increased focus on back office processes, systems and personnel. Regulatory developments, such as market risk capital requirements and guidelines, have also played their part in accelerating the adoption of increasingly sophisticated methodologies to analyze and monitor market risks. Technological advances have greatly aided the adoption of these more sophisticated systems. The move away from proprietary trading and towards customer-generated business has increased the emphasis on educating clients about the risks involved in various products. This process of education has extended internally within financial institutions. Increased awareness of risk management practices should reduce the likelihood of future large trading losses. As to the financial standing of Turkey's banking sector, Turkish banks have achieved a level of financial and institutional development not to be underestimated. But besides these strengths, there are various threats to the well being of the Turkish banking sector, which should be mentioned. Turkish banks are mostly exposed to credit risk, liquidity risk, interest rate risk, and foreign exchange risk. This is true even when there is no global crisis or macroeconomic risks stemming from political uncertainty. As a matter of fact, November 2000 and February crises showed the vulnerability of banks in Turkey. During the last two decades, the banking sector, which plays a prominent role in the Turkish financial system, has made significant progress in implementing structural changes towards a more financially liberalized Turkish economy. Combined with the effects of restructuring Turkish economy and the efforts for the integration to the modern world of finance, the Turkish banks achieved important changes in their institutional structures on the one hand, and in the quality of services and products on the other. In this very outward-oriented and closely supervised banking environment, the need for highly qualified managers and specialized personnel is obvious. With this in mind, Turkish Banks became more effective in their utilization of human resources. The number of university graduates and postgraduates in the banking sector has steadily increased over the last two decades, as has the level of professional training. The increase in the number of banks and qualified personnel, in turn, enhanced competition and contributed to broad utilization of new financial instruments and techniques. Furthermore, the banks were motivated to attain a dynamic structure through automation. During the last decade, Turkish banks became more automated and efficient, along with their foreign counterparts. For example, the number of ATMs in Turkey has increased from zero to over eight thousands in the last decade. Intense competition and a desire to integrate with global financial markets has driven banks to improve the quality and the variety of services through information technology and international payment systems. As a result of this, Turkish banks have started to provide interactive banking services to decrease their costs and increase efficiency of banking transactions. They are also part of the Electronic Fund Transfer system for their internal banking transactions and of SWIFT for external transactions. Parallel to the process of liberalizing the economy, Turkish banks have made significant progress in investments and in organizations abroad. They opened branches abroad and took important steps to increase their shares in international markets by acquiring financial participations and partnerships. As of June 2000, Turkish banking sector, including branches abroad, operates with the total asset size of 140.4 billion $, more than 8.000 branches and almost 170.000 personnel. The Turkish banking sector is also open to international competition. At present 25 foreign banks, including development and investment banks, constitute 31% of the total number of banks in the sector. The share of foreign banks has also increased during the past few years. While their share was 5.8% and 5.6% as the end of 1997 and 1998 respectively, it increased to 6.7% as of June 2000, representing the total asset size of 9.4 billion dollar. The majority of this share belongs to foreign commercial banks. At present, the Turkish banking sector has up-to-date technology and is equipped with highly qualified personnel to compete in the international arena. The result is a more transparent and well-functioning banking sector whose players have been progressively modernizing their operations in line with the developments in the global banking community. There is a significant growth potential in the Turkish banking sector. Banks will have to compete in an increasingly challenging environment. In the coming years, strategically and technically well-positioned banks will be able to utilize the growth potential of the sector. However, increasing competition and squeezed profit margins are expected to force banks to be more cost conscious. In order to increase profitability and efficiency, mergers and strategic alliances with foreign banks will be on the agenda of the sector. The integration process with the European Union will bring new challenges for Turkish banks to increase their efficiency and quality of their services by improving their distribution channels. Additionally, increasing compliance with the internationally accepted standards and other structural changes made in line with the integration process with the EU will attract foreign banks, which in turn will intensify the competition in the sector. Another significant step taken by Turkish authorities was the introduction of the recent disinflation program and the other restructuring efforts. Turkey has suffered from chronically high inflation for years and our economy is the last high-inflation economy among the OECD countries. High level of public deficits and fiscal imbalances, together with self-fulfilling inflationary expectations are the main causes of the inflation process. Financing of these deficits has accelerated money growth and stimulated high real interest rates. The most recent developments are a reflection of the fact that Turkey has dedicated itself to solve the above-mentioned problems. Turkey is fully aware of the fact that this chronic high inflation prevents the whole economy from settling on a sustainable high-growth path and from integrating with the global economy. The program has been supported by the structural reforms in four fundamental areas; namely banking sector, social security and agriculture and public finance. With the awareness of the fact that the soundness of the banking system is of vital importance in an environment where banks are major players in the financial system and are involved in international banking activities, Turkey is continuing to take measures to improve both the quality and the effectiveness of banking surveillance system on basis of the EU directives and BIS principles. The most radical change towards strengthening the supervision and financial structures of banks was the establishment of Banking Regulation and Supervision Agency (BRSA). Additionally, Central Bank of Turkey has pursued the most independent monetary policy possible. More recently, the first priority of the Central Bank has shifted from maintaining financial stability towards achieving price stability. Regarding the monetary policy implementation, the main pillars of the Central Bank's approach are the its transparency, its accountability and its predictability. Given the increasing importance of its economic presence and close relations with the countries worldwide, it is crucial that Turkey to improve its domestic markets to contribute to the efficient allocation of world resources. Before and after the crises, Turkey continued to implement structural reforms like risk management, internal control and auditing system. Beyond reforms in banking, a disinflation program should be put in order to realize robust economic fundamentals. In Turkey, a notable part of the agenda for economic and banking reform has been introduced in a very short period of time. Throughout the crisis environment, capital adequacy and erosion in shareholders' equity have become the most crucial issues in the banking industry. To ensure that banks maintain an adequate amount of capital on a consolidated and unconsolidated basis, against losses which may result from existing and potential risks, Banking Regulation and Supervision Board has quite recently issued a regulation on the measurement and assessment of capital adequacy of banks. Effective of July 1, 2002 capital charges for market risks will be included on a consolidated basis when calculating the capital adequacy ratio. All these regulations are to deal with the crisis and to restructure the banking system. They are constructed on the basis of international regulatory standards included in the recommendations of the Basel Committee on Banking Supervision. It is encouraging to see the regulatory environment of banking being synchronized with the internationally accepted standards. However, it should be stated the pace and density of reforming under the crisis environment and the time constraints related to implementation are of great importance to the well-being of the economy and financial system. The specific priorities in any given country or in a group of countries will often differ. Also, depending on the reform undertaken, the time required for implementation will differ considerably. For example, both establishing appropriate capital adequacy requirements and reforming the legal/ judicial system are essential to providing the basis for a stable, robust financial system. Legal/ judicial reform will often take much longer to achieve than revising capital adequacy requirements, but the long-term importance of such reform implies that work towards accomplishing it should start as soon as possible. When the capital levels are comprehended, it is claimed that higher capital adequacy ratios could help enhance banks' soundness and stability in the short run. However, this may result with some weaknesses in their earning capacities. If this happens, then it may take a long time for banks to regain their competitiveness. This prospect may then undermine their soundness and hence weaken their competitiveness further. This competitive disadvantage could become more serious if financial markets are opened up while the financial sector restructuring is being carried out because international banks entering the market could afford to maintain their capital adequacy ratios, as they are able to manage the quality and risk of their asset portfolios better than domestic banks. High capital adequacy requirements may also produce perverse effects on macroeconomic policy management. Knowing that economic recovery is imminent and could improve the quality of assets held by commercial banks and hence lessen their burden of holding a large amount of capital, policy-makers may be more inclined to reflate the economy than re-capitalize the banks. There is no doubt that if a banking system impedes macroeconomic stability, the correction of this weakness probably requiring far-reaching measures, will be inevitable sooner or later. Deferral of needed macro-stabilization will not by itself ease the position of the banks. Therefore, although it would be foolhardy to imply that a general prescription is valid for all cases, the presumption must be that measures necessary for macro-stability should not be deferred, and at the same time the weak banks should be promptly intervened, with whatever liquidity support is needed for the system to offset depositor panics. In this sense, bank rescue policy should normally be subordinate to macro-stabilization of the economy. It should be recognized that these incremental improvements will be more drastic for some countries/ institutions and less drastic for others. The general principle is that the complexity and focus of both the supervisory examination and capital requirements should be determined by the complexity, diversity and perhaps the scale of the economy/ organization being examined. This also suggests not only different approaches across nations but also different approaches within nations. Thus, a one-size-fits all supervisory and regulatory framework may be inconsistent with the existing and evolving banking structure. Banks are just too different, with different risk profiles, risk controls, strategies and approaches to managing risks to be supervised and regulated by one yardstick. And the forces of volatilities in our environment necessitate an integrated approach in all dimensions of business risks. At the Central Bank of Turkey, a risk management division was established three years ago. The need for such a division came as a result of multiple factors. These factors can be grouped into two as external and internal. The external ones, as mentioned before, are rising volatilities in financial markets, rapid developments in information technology, huge increase in trading activity and development of new financial instruments along with the globalization of financial markets. The internal factors are accumulation of net reserves starting from 1997 and the increased responsibility of our bank in terms of its leading role in the Turkish financial markets. As the work on risk management has progressed during the 1999 establishment process, reserve management needed to be restructured to have an efficient risk management. Although, with the concern of having enough liquidity and preserving safety, the return factor is considered as well. Therefore, the reserves were separated into different tranches serving different purposes, one for operational, one for liquidity and one for investment as in the case of the most central banks changing their approach to reserve management. Within this framework, a performance benchmark for the reserves to evaluate performance on a risk-adjusted basis was developed. The benchmark reflecting the neutral position has been constructed in line with the objectives, the asset-liability structure and the liquidity needs of the Bank for a one-year period. It is been reconsidered periodically. The Risk Management Division in the Central Bank of Turkey is in the process of establishing a system to carry out risk analysis and to feed the results to the appropriate units. For the last year or so, duration and Value at Risk (VaR) figures reflecting interest rate and currency risks of the FX reserves, and liquidity indicators such as current ratio (percentage of liquid assets in total of liabilities) are being observed. However, these reports are not yet parts of a comprehensive risk measurement and control system. Although they give an idea of the general level of market and liquidity risk levels, the actual risk exposure will be clearly seen only after the reserves portfolio is restructured and the benchmarks are included in these reports. The risk management process related to market risk that we plan includes daily marking to market of benchmark portfolios; monitoring risk limits determined in terms of currency and duration limits; daily measurement of actual portfolio's VaR figures for currency and interest rate exposure; monitoring liquidity ratios and reporting these figures to the top management weekly including stress testing report. There is no specified global risk tolerance limit but our institutional objectives and constraints are reflected in portfolio benchmarks. In terms of performance evaluation comparison of actual and benchmark portfolios returns are going to be monitored daily and reported to the top management periodically. For credit risk management side, a transaction limit is assigned to each counter party, covering all types of credit risks and market risks. The limits are marked to market daily and reflect the amount of exposure that the bank is willing to take with each counter party. The credit limits are set by employing an internal scoring model that incorporates the counter party's external credit ratings, financial information, and some other qualitative information such as the quality of relationship with our bank and the support status, i.e. the possibility of getting help from the government in case of financial difficulty. The credit rating of the country in which the bank operates is also considered. Reports about limit monitoring are produced regularly. It is of great importance to have an efficient risk management to protect reserves from financial instabilities. Rapid changes should be watched in terms of technological developments and of economic conditions very closely. Banks must adapt themselves to these changes right away. All kinds of risks have been thoroughly monitored by the supervisory authorities, which put preventive measures in place before the effects of any problems that were found could threaten financial stability. Under this regulatory system, the banks must submit annual, quarterly, and even daily financial data to the Central Bank and the Treasury. Besides frequent financial evaluations of banks by off-site examiners, on-site examinations are conducted to verify the accuracy and reliability of the data reported and clarify any special issues found during off-site examinations. A sound economy must be based on well-functioning real and financial sectors, and there can be no doubt that, in times to come, we will have to give still more thought to reducing financial risks and keeping them from interfering with the proper functioning of the system. If competition, volatility, globalization, and stresses threaten to pressure the banking industry into resorting to bad risk-taking practices, the responsible authorities and supervisors must take whatever steps are necessary to restore financial stability. The on-going process of globalization, along with the revolution in information technology, is likely to continue in the future. One consequence of this trend is the intensifying competition at the global level. The soundness of individual financial systems clearly affects the resilience of the international financial system as a whole. Banks should devote their efforts towards creating a healthier global environment by minimizing the volatility of international capital flows and the risk of contagion. More effective supervision and surveillance of banking systems is of the greatest importance in today's international banking environment and the emphasis of the recent supervisory changes has been moving from the rules-based method of supervision towards a risk-focused supervision. Additionally, the globalization of financial markets led to difficulties in auditing cross-border transactions mainly due to lack of cooperation between supervisory authorities. However, in recent years, care has been given to overcome inter-country problems and increase cooperation. Success of countries in integrating into the global financial system and in fulfilling the requirements of globalization will depend on deeper international cooperation between national and international agencies. At present, there exist several countries and nations that are not yet benefiting from the globalization. Many obstacles stand in their way towards integration into the global economy. In an increasingly globalized world economy, financial sector stability is most likely to be achieved when prudent international standards are met and when markets operate competitively, professionally and transparently, according to sound principles and practices. Strengthening the supervisory and regulatory framework towards achieving a sound and efficient global banking system should be a universal goal. In this sense, the works that have been accomplished by the Basel Committee, FSI, Financial Forum etc. so far should be regarded as innovative and constructive in the process of harmonization of rules and standards internationally. Effective supervision combined with a multi-dimensional study of past experiences and all the micro and macro level indicators will help Turkey to find ways to handle what globalization brings. Turkey needs more progressive studies on platforms like the one at the present that will help to develop new ideas and ways for responding promptly and correctly to the challenges of globalization. Turkey has to look for solutions in the regulations that will be imposed on the financial sector and try hard to make them strict enough to prevent circumvention and excessive risk taking. It should be noted that Turkish banking sector hit the ground because of a poor misguided approach to bank management that hardly ever had risk management within. The system should be liberal enough to promote innovation and growth without postponing the implementation of standards, this time.
Keywords: Banka ve bankacılık; Bankacılık-risk Yönetimi; Ekonomi; Finansman ekonomisi